Multiplex PCR assay and simple preparation method for stool specimens detect enterotoxigenic Escherichia coli DNA during course of infection. - Stacy-Phipps, S (1995)
Infection with enterotoxigenic Escherichia coli (ETEC) is a common cause of diarrhea among travelers and residents of developing countries. ETEC produces either a heat-stable toxin or a heat-labile toxin, or both, encoded by plasmid-borne ST and LT genes, respectively. Diagnosis of infection with this subclass of E. coli can be performed with oligonucleotide hybridization probes; however, the sensitivity and specificity of this method are insufficient. A nonradioactive multiplex PCR assay that provides a sensitive and specific method for detecting the presence of either or both toxin genes has been developed. A simple procedure that removed inhibitors of the PCR while efficiently releasing ETEC DNA from stool specimens for subsequent amplification was used. The results for samples from a human volunteer study of ETEC infection indicated that this method of sample preparation results in greater clinical sensitivity than conventional total nucleic acid extraction and ethanol precipitation. Detection of ETEC by a multiplex PCR assay in stool specimens directly processed with a glass matrix and chaotropic solution had greater sensitivity than culture.